(untitled) (Zdravstveni glasnik, 2024)
Introduction: Many epidemiological studies have shown a connection between vitamin D deficiency and increased incidence of type 1 diabetes. Objective: The aim of this study is to determine the impact of vitamin D levels in children with newly diagnosed type 1 diabetes, taking into account the following parameters: gender, place of residence, positive/negative family history, comorbidities. Respondents and methods: The research was conducted through a retrospective analysis of the medical records of the Children’s Disease Clinic of the University Clinical Hospital Mostar. The research included a sample of 30 children diagnosed with type 1 diabetes, treated at the Department of Endocrinology and Metabolic Diseases, Clinic for Children’s Diseases, University Clinical Hospital Mostar. Results: The research consisted of 30 participants treated at the Department of Endocrinology and Metabolic Diseases, Clinic fo Children’s Disease. The sample consists of 40% (n=12) male respondents and 60% (n=18) female respondents. Slightly more than half of the respondnents, 53.3% (n=16) lived in the city, while the remaining 46.7% (n=14) lived in the countryside. Statistical analysis of the patients with newly diagnosed type 1 diabetes, showed that there were significantly more patients (70%) with positive family history of diabetes mellitus than those with negative. In this study, 26.7% (n=8) patients with newly diagnosed type 1 diabetes had comorbidities, compared to 73.3% patients without comorbidities (n=22). Patients living in rural areas had significantly higher values of vitamin D3 concentration compared do those who lived in urban areas. Conclusion: 83.3% of subjects with newly diagnosed type 1 diabetes have a reduced level of vitamin D at the time of diagnosis. Numerous studies have shown a link between vitamin D deficiency and an increased risk of developing diabetes. Due to all of the above, supplementation and control of vitamin D is recommended, especially in children who have a risk in the form of positive family history and comorbidities such as Hashimoto’s thyroiditis, and celiac disease from an early age for the purpose of prevention.